DIAGNOSIS OF SPIRITUAL EDUCATION OF STUDENTS SENIOR CLASSES - N.V. Dolgaya (Academy of Cognitive and Natural Sciences, 2022)
The diagnostic methods of senior pupils spiritual development are exposed in the article.